2019
DOI: 10.3390/jcm8060817
|View full text |Cite
|
Sign up to set email alerts
|

High TSH Level within Normal Range Is Associated with Obesity, Dyslipidemia, Hypertension, Inflammation, Hypercoagulability, and the Metabolic Syndrome: A Novel Cardiometabolic Marker

Abstract: (1) Background: Overt and subclinical hypothyroidism has been associated with increased cardiometabolic risks. Here we further explore whether thyroid function within normal range is associated with cardiometabolic risk factors in a large population-based study. (2) Methods: We screened 24,765 adults participating in health examinations in Taiwan. Participants were grouped according to high-sensitive thyroid-stimulating hormone (hsTSH) level as: <50th percentile (0.47–1.48 mIU/L, the reference group), 50–60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 47 publications
(61 reference statements)
2
47
4
Order By: Relevance
“…Similar to our study, significant positive associations between TSH, AST, and total bilirubin levels have been reported previously [5,6]. A previous study suggested the role of high TSH levels as a cardiometabolic risk marker and that dyslipidemia, hyperglycemia, and liver abnormalities were associated with high TSH levels [23]. In the present study, however, we could not evaluate such laboratory findings.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Similar to our study, significant positive associations between TSH, AST, and total bilirubin levels have been reported previously [5,6]. A previous study suggested the role of high TSH levels as a cardiometabolic risk marker and that dyslipidemia, hyperglycemia, and liver abnormalities were associated with high TSH levels [23]. In the present study, however, we could not evaluate such laboratory findings.…”
Section: Discussionsupporting
confidence: 76%
“…Elevated TSH levels and hypothyroidism have been associated with the pathogenesis of NAFLD [23][24][25]. Other factors such as obesity and metabolic syndrome were also considered risk factors for subclinical hypothyroidism [26].…”
Section: Discussionmentioning
confidence: 99%
“…Before this study, we used the similar data to analyze the relationship between serum uric acid and CKD in the general population, and concluded that time-mean serum uric acid is an independent risk factor for CKD [18]. Dyslipidemia and hyperuricemia are important diseases that affect human health [19]. Therefore, we specifically studied the relationship between dyslipidemia and CKD.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Jiaoyue et al found that after adjusting for age and other confounding factors, there is no correlation between TSH level and blood lipids [10]. However, a linear dose-dependent correlation between high TSH level in the normal range and dyslipidemia, possibly mediated by the effect of thyroid hormones on insulin sensitivity, was revealed in a large population-based study [11]. In patients with normal thyroid function and newly diagnosed asymptomatic coronary heart disease, the increased TSH level may have adverse effects on blood lipids and may also be a risk factor for hypercholesterolemia and hypertriglyceridemia [12].…”
Section: Introductionmentioning
confidence: 99%